Diagnosis of Chediak Higashi disease in a 67‐year old woman. Issue 12 (29th September 2020) - Yarnell, David S.; Roney, Joseph C.; Teixeira, Cláudia; Freitas, Maria I.; Cipriano, Ana; Leuschner, Pedro; Krzewski, Konrad; Stephen, Joshi; Dorward, Heidi; Gahl, William A.; Gochuico, Bernadette R.; Toro, Camilo; et al.
Abstract: Chediak‐Higashi disease is a rare disease caused by bi‐allelic mutations in the lysosomal trafficking regulator gene, LYST . Individuals typically present in early childhood with partial oculocutaneous albinism, a bleeding diathesis, recurrent infections secondary to immune dysfunction, and risk of developing hemophagocytic lymphohistiocytosis (HLH). Without intervention, mortality is high in the first decade of life. However, some individuals with milder phenotypes have attenuated hematologic and immunologic presentations, and lower risk of HLH. Both classic and milder phenotypes develop progressive neurodegeneration in early adulthood. Here we present a remarkable patient diagnosed with Chediak‐Higashi disease at age 67, many decades after the diagnosis is usually established. Diagnosis was suspected by observing the pathognomonic granules within leukocytes, and confirmed by identification of bi‐allelic mutations in LYST, reduced LYST mRNA expression, enlarged lysosomes within fibroblasts, and decreased NK cell lytic activity. This case further expands the phenotype of Chediak‐Higashi disease and highlights the need for increased awareness. Individuals with milder phenotypes may escape early diagnosis, but identification is important for close monitoring of potential complications, and to further our understanding of the function of LYST.